Marrying a Billionaire: Studying US American billionaires' family biographies using the Forbes World's Billionaires List, 2010–2022 - Ria Wilken (Review of Economics of the Household, 2025)
Despite the recent findings on the inequality-increasing effect of homogeneous marriages, the growing body of literature on `the super-rich', has missed out on illuminating contemporary global wealth inequality levels from a marital choice perspective. Not much is known about family formation at the top of the wealth distribution. By combining Forbes billionaires rich list data and billionaires' Wikipedia articles with qualitative data, the paper presents a unique dataset capturing all US American billionaires ( n 0.167em=0.167em948) and their spouses. The results suggest deeply ingrained traditional role allocations in billionaire couples. Female billionaires appear to be more likely to have a partner in the same upper-class fraction than male billionaires, who appear to be more liberal regarding their spouses' class positions. By shedding light on the unique marriage demographics of the super-rich, the paper supports the importance of dynasty-making family strategies and social closure for understanding the economic elites of our times.
Keywords: 330; Billionaires; Homogamy; Gender; Wealth; Inequality